2007
DOI: 10.1073/pnas.0707148104
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of a bicyclobutane fatty acid by a hemoprotein–lipoxygenase fusion protein from the cyanobacterium Anabaena PCC 7120

Abstract: Biological transformations of polyunsaturated fatty acids often lead to chemically unstable products, such as the prostaglandin endoperoxides and leukotriene A 4 epoxide of mammalian biology and the allene epoxides of plants. Here, we report on the enzymatic production of a fatty acid containing a highly strained bicyclic four-carbon ring, a moiety known previously only as a model compound for mechanistic studies in chemistry. Starting from linolenic acid (C18.33), a dual function protein from the cyanobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…Initially, we experimented with HPLC under cold conditions (silica column, hexane/diethyl ether solvent, 100:5, v/v, run at 210-15°C) as used previously for isolation of allene epoxides (17). Later, the use of HPLC conditions previously developed for chromatography of LTA 4 proved more satisfactory, either SP-HPLC of methyl esters using triethylamine in the solvent (14,18) or our modification of a reversed-phase HPLC (RP-HPLC) procedure, suitable for methyl esters or acids (1,19). For SP-HPLC, an Altex silica guard column (5 mm, 45 3 4.6 mm) was run with a solvent of hexane/triethylamine (100:0.5, by volume) eluted at 3 ml/min.…”
Section: Preparation and Purification Of The Unstable Epoxidementioning
confidence: 99%
See 3 more Smart Citations
“…Initially, we experimented with HPLC under cold conditions (silica column, hexane/diethyl ether solvent, 100:5, v/v, run at 210-15°C) as used previously for isolation of allene epoxides (17). Later, the use of HPLC conditions previously developed for chromatography of LTA 4 proved more satisfactory, either SP-HPLC of methyl esters using triethylamine in the solvent (14,18) or our modification of a reversed-phase HPLC (RP-HPLC) procedure, suitable for methyl esters or acids (1,19). For SP-HPLC, an Altex silica guard column (5 mm, 45 3 4.6 mm) was run with a solvent of hexane/triethylamine (100:0.5, by volume) eluted at 3 ml/min.…”
Section: Preparation and Purification Of The Unstable Epoxidementioning
confidence: 99%
“…This is an unusual LOX activity, forming products enantiomeric to the 9S-LOX of plants (5), and characterized earlier in Hydra vulgaris (6), in the marine alga Ulva conglobata (7), and as an activity of Gersemia fruticosa arachidonate 11R-LOX (8). We showed that the catalaserelated domain converts the 9R-hydroperoxide of a-linolenic acid to two unstable epoxides that we isolated and characterized (1). One is an allylic 9,10-epoxide with C13-C16 of the carbon chain cyclized into a [1.1.0]bicyclobutane, a unique structural motif in biology.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…These enzymes are significantly smaller than the described animal and plant LOXs and a number of them have so far been identified in cyanobacteria (35,(42)(43)(44)(45). Alignment of the predicted amino acid sequence of CspLOX2 with that of Mn-LOX shows conserved features, e.g.…”
Section: Discussionmentioning
confidence: 99%